Methods Of Preparing For A Fight In Thai Boxing - Nizamova Shaxnoza Ravshonovna (Genius Publishing Group, 2024)
The article discusses the functionality of a Thai boxer. Methods for developing the physical components of an athlete are analyzed
Keywords: Thai boxing; Muay Thai; technique; endurance